BORDER DISPUTE BETWEEN INDIA AND CHINA: AN ANALYTICAL STUDY - Mamta Devi; Kumar, Manu (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The two biggest and most populated nations in the world are China and India. However, both nations are embroiled in a territorial dispute concerning the sovereignty of several significant and smaller segments of land along their shared border. This border dispute has its origins in the colonial delineation of state boundaries especially in the Himalayan region towards the west the middle sector, and the eastern sector. It is common for mistrust to arise periodically across the 3,488-kilometer-long Sino-Indian border. The 1914 Shimla convention between British India and Tibet Created the McMahon line in the eastern sector And was executed without the approval of the People’s Republic of China (PRC). PRC claims that Tibet was never autonomous at the time of the similar convention thereby rejecting this deal. These contested areas were the focus of the 1962 PRC-Indian War in which Chinese forces crossed the McMahon line in the east and attacked Indian border positions In Ladakh in the West. In 1967 there was a brief board conflict in the Sikkim areas. Potential confrontation over the divergent (LAC) Line of Actual Control was well minimized In 1987 and again in 2013 but tension resurfaced in 2017 when Chinese and Indian servicemen were hurt who stopped in 2020 several combat Breaks out resulting in several deaths in June of that year.